2019
DOI: 10.1111/jan.14045
|View full text |Cite
|
Sign up to set email alerts
|

The role of patients in the delivery of safe care in hospital: Study protocol

Abstract: Aim: This paper outlines the protocol for a study aimed at exploring perspectives about the role of patients' in the delivery of safe care in hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In this Canadian study, survey methods and focus groups were conducted with patients (217 survey responses and 10 in focus groups). (d) One study protocol for an exploratory qualitative study about patient and provider perspectives about the role of patients in safe care was also found 54 . (e) Nine text and opinion papers : These items include books, opinion articles and a white paper.…”
Section: Resultsmentioning
confidence: 99%
“…In this Canadian study, survey methods and focus groups were conducted with patients (217 survey responses and 10 in focus groups). (d) One study protocol for an exploratory qualitative study about patient and provider perspectives about the role of patients in safe care was also found 54 . (e) Nine text and opinion papers : These items include books, opinion articles and a white paper.…”
Section: Resultsmentioning
confidence: 99%
“…Another challenge of the Iranian healthcare system is staff shortages, the financial pressures experienced by hospitals, lack of senior management support for patient safety culture and lack of systematic approach for reporting errors [43,44] which means patient safety is seen as a low priority by managers. For patient safety to be effective, there is a need for continuous educational advancement at every level of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…This was a qualitative study based on semi‐structured interviews and was conducted in Iran during February–April 2019. A more detailed outline of the methods that were adopted and the research questions that were posed may be found in the study protocol document (Chegini, Janati, Babaie, & Pouraghaei, ).…”
Section: Methodsmentioning
confidence: 99%